2016
DOI: 10.2903/j.efsa.2016.4524
|View full text |Cite
|
Sign up to set email alerts
|

Risks for public health related to the presence of Bacillus cereus and other Bacillus spp. including Bacillus thuringiensis in foodstuffs

Abstract: The Bacillus cereus group, also known as B. cereus sensu lato, is a subdivision of the Bacillus genus that consists of eight formally recognised species: B. cereus sensu stricto, B. anthracis, B. thuringiensis, B. weihenstephanensis, B. mycoides, B. pseudomycoides, B. cytotoxicus and B. toyonensis. The current taxonomy of the B. cereus group and the status of separate species mainly rely on phenotypic characteristics. Bacillus thuringiensis strains display a similar repertoire of the potential virulence genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 373 publications
4
84
0
Order By: Relevance
“…B. cereus causes two types of foodborne illness, an emetic (vomiting) intoxication due to the ingestion of a toxin (cereulide) pre-formed in the food and a diarrheal infection due to the ingestion of bacterial cells/spores which produce enterotoxins in the small intestine [42]. More recently, the European Food Safety Authority (EFSA) panel on biological hazards (BIOHAZ) [43] reported that most cases of foodborne diseases have been associated with greater than 10 5 CFU/g of B. cereus in the food vehicle, with some cases ranging to 10 8 CFU/g for diarrheal infection.…”
Section: Selection Of a "Short List" Of Significant Hazardsmentioning
confidence: 99%
“…B. cereus causes two types of foodborne illness, an emetic (vomiting) intoxication due to the ingestion of a toxin (cereulide) pre-formed in the food and a diarrheal infection due to the ingestion of bacterial cells/spores which produce enterotoxins in the small intestine [42]. More recently, the European Food Safety Authority (EFSA) panel on biological hazards (BIOHAZ) [43] reported that most cases of foodborne diseases have been associated with greater than 10 5 CFU/g of B. cereus in the food vehicle, with some cases ranging to 10 8 CFU/g for diarrheal infection.…”
Section: Selection Of a "Short List" Of Significant Hazardsmentioning
confidence: 99%
“…Numerous impact studies of field application rates and acute intoxications have shown that Bt bioinsecticides are safe or have a limited impact on non-target vertebrates and invertebrates, and associated species communities 19,20 . However, the increasing use of bioinsecticides based on Bt spores and toxins has recently raised concern 21 and led to the assessment of their potential effects on non-target species, such as auxiliary insects of biological control 22 , pollinators 23 and species communities which share their habitat with Bt-targeted insect pests [24][25][26] . There is growing evidence of direct and indirect cross-effects of Bt bioinsecticide formulations and Bt-Cry and Cyt toxins across insect species and orders, or even across phyla, suggesting that Bt targeting is only partly specific 12,26,27 .…”
mentioning
confidence: 99%
“…In adults, B. cereus is involved mainly in gastrointestinal infection and is the third most common cause of food poisoning ( 1 ). Rarely, this bacterium causes invasive or fatal infections in high-risk patients, such as immunocompromised adult patients and preterm neonates who have an immature immune system that is mostly restricted to innate immunity ( 2 4 ).…”
mentioning
confidence: 99%